Safe, supported, and empowered. (December 2022) - White, Annie M.; Weiss, John Kenneth
Many effective strategies exist to keep students safe, supported, and engaged in school. Restorative practice (RP) is a powerful approach for achieving these goals as it elevates student voice and can strengthen school climate. Annie M. White and John Kenneth Weiss share findings from an initiative through which high school student-faculty teams learned strategies to use RP practices and incorporate student voice to improve school climate. After two years, students gained the confidence to work for school change. They offer implementation recommendations, including prioritizing relationship-building, reaching a critical mass, and providing structure for engagement. Ultimately, they found that student voice and engagement may be key to improving school climate .